Design Optimization of Micro Air Launch Vehicle Using Differential Evolution - Aldheeb,Mohammed Abdulmalek (2012)
Abstract: In this paper, we have used the differential evolution to optimize the design of a Micro Air Launch Vehicle and its launch trajectory. Since trajectory design of a launch vehicle requires prior knowledge of the masses and propulsion performance parameters of the Micro Air Launch Vehicle, whereas the vehicle design requires prior knowledge of the required velocity (ΔV) to insert the required payload into the target orbit, a two-step optimization cycle was adopted. A Micro Air Launch Vehicle was designed to launch a 20-kg payload into a 400-km circular polar orbit. The preliminary design of the Micro Air Launch Vehicle was conducted given the required ΔV, which was obtained from trajectory optimization, and then applied in mission analysis to obtain the initial masses. These initial masses were used in the vehicle design to get the performance and geometry parameters. The objective function of the Micro Air Launch Vehicle design optimization is to minimize the initial mass under specified constraints on the insertion orbit. The objective of trajectory optimization is to maximize the payload mass under constraints on orbit specifications and design variables. For the 20-kg payload mass, the optimal initial mass is 1267.8 kg and optimal payload is 20.6 kg, which slightly exceeds the mission requirements.